Electrochemical Preparation and Characterization of Zinc Oxide Nanoparticles as a Model for Drug Delivery in Pharmaceutical Compounds - Aqeel Mahdi Alduhaidahawi (Journal of Global Pharma Technology, 2018)
Zinc oxide nanoparticles (ZnO NPs) were prepared by electrochemical method in solution contains NaNO3 as electrolyte and Polyvinylpyrrolidone (PVP) as stabilizer. The prepared ZnO NPs were characterized by EDX, SEM, TEM, and AFM studies .EDX-Spectrum of ZnO nanoparticles exhibited signals of zinc and oxygen only, and that means the sample of ZnO NPs having high purity. SEM micrographs givesa homogeneous particles distribution and having sheets like structure. From TEM study the size of ZnO NPs was found to be about 60 nm and the shape of nanoparticles was a bipyramid like shape. The average size of synthesized ZnO NPs from AFM study was found to be 60.99 nm; this result was agreement with result that obtained from TEM.Keywords: Electrochemical Preparation, Zinc Oxide Nanoparticles, AFM; SEM; TEM.